ANALISIS PERBANDINGAN KONSEP MAHAR MENURUT PEMIKIRAN IMAM SYAFI’I DAN IMAM HANAFI - Fikan, Wafa’ Atqiya’; Mustofa, Imron (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The dowry is a gift given by the groom to the woman he will marry, which then becomes entirely the property of his wife. The dowry given at the time of marriage undoubtedly holds value and benefits. This normative legal research, which uses only secondary and primary data, refers to legal sources that have binding authority, such as the Qur'an, hadith, and the views of the Imam Shafi'i and Imam Hanafi schools of thought. Imam Al-Shafi'i opines that there is no minimum limit for anything that can be valued in trade, and therefore, it can be used as a dowry. Thus, according to Imam Al-Shafi'i, there is no minimum limit, meaning that a person is free to give according to their means, while Imam Hanafi believes that the minimum dowry is ten dirhams and that the dowry can take the form of goods or services that are considered additional obligations in a marriage contract. This study suggests that the community, particularly those who follow the Shafi'i school of thought, should implement this concept in real life.